Low legal awareness as a criminogenic factor - Ondicová , Magdaléna; Horková , Gabriela (Scientific Journal of Bielsko-Biala School of Finance and Law, 2020)
The subject of the presented paper is the issue of low legal awareness, which has long been described by experts as a significant criminogenic factor in the population living in the Slovak Republic. Based on current data obtained from the public opinion survey conducted through a questionnaire, the primary goal of which was to determine the level of legal awareness in the Slovak population, it is possible to obtain at least a partial overview of the level of legal awareness in the general public. Civil and criminal law are the main interests of the presented article, as the knowledge base of the particular field is an integral part of the daily existence of an individual living according to the law in the society. The acquired knowledge and interpretation of relevant information obtained from research is undoubtedly important for the needs of practice, as the authors provide insight into current problems in the particular field, the authors also present a proposal for specific recommendations for the system of further education